2002
DOI: 10.1192/pb.26.2.44
|View full text |Cite
|
Sign up to set email alerts
|

The role of the doctor when a patient commits suicide

Abstract: The literature concerning psychiatrists' responses to patient suicide is sparse (Brown, 1987; Chemtob et al, 1988; Alexander et al, 2000) but even less attention has been given to the psychiatrist's role in the aftermath of such an event. Psychiatrists infrequently discuss their own experience of patient suicide with their colleagues, either at an individual level (Kaye & Soreff, 1991) or in group settings such as team meetings (Ruben, 1990). This is all the more remarkable when one acknowledges that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…Notably, "self-relevant" may also be interpreted in the career context, such that a death with legal implications (e.g., suicide) is likely to be more associated with heightened emotions (Campbell & Fahy, 2002;Hendin et al, 2000) than a nonlegally implicated death.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Notably, "self-relevant" may also be interpreted in the career context, such that a death with legal implications (e.g., suicide) is likely to be more associated with heightened emotions (Campbell & Fahy, 2002;Hendin et al, 2000) than a nonlegally implicated death.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They highlight that doctors in the UK who need more formal assistance can look to the British Medical Association, the Royal College of Psychiatrists and the National Counselling Ser vice for Sick Doctors. Campbell & Fahy (2002) also address the role of the doctor following a patient's suicide and point out that effects on the psychiatrist may be compounded by an obligation to address the needs of other team members (e.g. psychiatric trainees).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…It has been seen that the suicide of a patient generates changes in health care workers both at their work and personal life. Significant among psychiatrists are feelings of professional failure, questions about their expertise, concerns about legal repercussions and changes in their professional practice (Campbell & Fahy, 2002;Grad & Michel, 2005;Grad, Zavasnik & Groleger, 1997;Hendin, Lipschitz, Maltsberger, Haas & Wynecoop, 2000;Henry, Séguin & Drouin, 2008;Horn, 1994). However, it has been shown that to the extent that physicians acquire greater professional experience, the guilt, low self-esteem and social withdrawal experienced after the suicide of a patient decreases (Chemtob et al, 1988).…”
Section: Introductionmentioning
confidence: 99%